Análisis de una alternativa química no convencional para optimizar el factor de recobro en el campo Yaguará mediante simulación numérica (2019)
The present study starts from an understanding and an understanding of the characteristics and needs of the Yaguará Field, and then goes to the analysis and description of two non-conventional chemical alternatives of tertiary recovery in order to select the most optimal option for the field, taking into account Mainly counts the criteria and objectives of the company.